The effect of pack-carburizing method to the hardness of AISI 1050 steel / Siti Morni Ramtan and Zeti Akhtar Mohamad - Ramtan, Siti Morni; Mohamad, Zeti Akhtar (1994)
AISI 1050 steel (roller chain) besides others is an important component in vehicles especially motorcycle. Many reports showed that low quality, motorcycle roller chain can easily break and cause fatal accident to the rider. In order to avoid the accident due to roller chain failure, the components should have certain quality as specified by Malaysian Standards. The objective of this project is to get the optimum hardness of the AISI 1050 steel (roller chain). To obtain the required hardness, pack-carburizing is carried out both at the laboratory and factory.